2023
DOI: 10.15823/p.2022.148.11
|View full text |Cite
|
Sign up to set email alerts
|

Graphic Organizers in an Online Learning Environment: Its Influence to Students’ Cognitive Load and Knowledge Gain

Abstract: The study investigates how graphic organizers influence the level of cognitive load and knowledge gained by the students at Quezon City University during the 1st semester, Academic Year 2021–2022 in an online learning environment. The one-group pretest-posttest design was utilized in the study. Results show that by using graphic organizers, students’ level of cognitive load and knowledge gain have improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The ANOVA test obtained a significance of 0.467 > 0.05, meaning that there was no difference in students' ability to write opinion essays in the three groups on their self-efficacy with the application of the developed GO (See Table 7). This result contradicts several previous studies which found a relationship between academic achievement and selfefficacy, where high-achieving students have high self-efficacy, and vice versa (Boroumand et al, 2020;Eissa, 2012;Estacio, 2021;Nobahar et al, 2013). Likewise, the application of GO in courses increased students' learning outcomes from low and moderate to moderate and high levels, along with an increase in self-efficacy (Boroumand et Based on the results above, no correlation was found between students' writing ability and their self-efficacy.…”
Section: B the Effects Of Using The Developed Go On Students' Writing...contrasting
confidence: 93%
See 2 more Smart Citations
“…The ANOVA test obtained a significance of 0.467 > 0.05, meaning that there was no difference in students' ability to write opinion essays in the three groups on their self-efficacy with the application of the developed GO (See Table 7). This result contradicts several previous studies which found a relationship between academic achievement and selfefficacy, where high-achieving students have high self-efficacy, and vice versa (Boroumand et al, 2020;Eissa, 2012;Estacio, 2021;Nobahar et al, 2013). Likewise, the application of GO in courses increased students' learning outcomes from low and moderate to moderate and high levels, along with an increase in self-efficacy (Boroumand et Based on the results above, no correlation was found between students' writing ability and their self-efficacy.…”
Section: B the Effects Of Using The Developed Go On Students' Writing...contrasting
confidence: 93%
“…Layered controllers have been proven successful in remediating the academic achievement of students at the elementary school to university levels, both those with special needs (Boykin et Estacio (2021) confirmed that the self-efficacy of the treatment group increased after being exposed to several types of GO in the classroom. In other words, teaching and learning process that combines various types of layered tools "have been shown to bring gains in student self-efficacy.…”
Section: B Graphic Organizers and Self Efficacymentioning
confidence: 99%
See 1 more Smart Citation